PENGGUNAAN KONSEP RULES-IN-USE OSTROM DALAM ANALISIS PERATURAN PEMANFAATAN AIR DI KAWASAN KONSERVASI: STUDI KASUS TAMAN NASIONAL GUNUNG GEDE PANGRANGO - Rudy Dwi Siswantoro; Hariadi Kartodihardjo; Hendrayanto Hendrayanto; Dudung Darusman (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2021)
This study aims to analyze the substantial weaknesses of water utilization regulations in wildlife reserves, national parks, forest parks, nature tourism parks, and their effects on individual or organizational decision[1]making and actions. The research location is in the area of Taman Nasional Gunung Gede Pangrango (TNGGP). The analysis of this research is limited to Environment and Forestry Ministerial Regulations No. P.18/MENLHK/ SETJEN/KUM.1/4/2019, Law No. 17 of 2019, and Environment and Forestry Ministerial Regulations No. P.6/ MENLHK/SETJEN/KUM.1/1/2020. Regulatory analysis is carried out by identifying the characteristics of content of the regulations and comparing them with the conditions of water utilization in TNGGP to find out the implications of regulations on participant behavior and performance. Issues and problems are collected through interviews with participants. Furthermore, the regulations are analyzed using Ostrom's rules-in-use concept. The findin , based on the concept is that there is a discrepancy in the three regulations that all regulate water utilization permits in the conservation areas. This is mainly due to weak institutional strengthening among decision makers as well as laws and regulations made according to the interpretation of the government which often do not consider the conditions of the community.